PERBANDINGAN HASIL BELAJAR BAHASA INGGRIS SISWA MENGGUNAKAN METODE INTERAKTIF DENGAN METODE KONVENSIONAL (Studi Kasus Siswa Kelas I dan II SD Islam Al Azhar 15 dan SD Islam Nurfatahillah di Kecamatan Pamulang, Tangerang Selatan) - Lia Herlina; Umi Rusilowati; Rasmadi . (Universitas Pamulang, 2015)
COMPARISON OF STUDENTS LEARN ENGLISH USING INTERACTIVE WITH CONVENTIONAL METHODS (A Case Study of Grade I and II SD Islam Al Azhar 15 and SD Islam Nurfatahillah in the district Pamulang, South Tangerang). The result shows that: from the result of interview and discussion shows that students’ interest in learning English is higher when using interactive CD method than the speech method, so this affected students’ learning achievement in both elementary schools. The statistical calculation of learning achievement of both elementary schools shows that the average score of students’ learning achievement at Al Azhar 15 Elementary School through speech method is 92.05 and its deviation standard is 5.89, while the average score of students’ learning achievement in experiment class through interactive method is 93.95 and its deviation standard is 4.97. The average score of the second grade of controlled class through speech method is 84.21 and its deviation standard is 4.08 while students’ learning achievement of experiment class is 92.29 and its deviation standard is 6.64. Meanwhile, the average score of second grade students’ learning achievement in controlled class at Nurfatahillah Elementary School through speech method is 86,59 and its deviation standard is 13,93, while the average score of students’ learning achievement in the experiment class is 91,24 and its deviation standard is 8,66. According to the statistical calculation, it can be seen that there is improvement on the average score of all classes at both elementary schools after using interactive method and interactive CD “ PLAYING WHILE STUDYING TOGETHER WITH BEBI”. The calculation of deviation standard which is inverse with the average score shows that the sameness of experiment classes’ test achievement of both Elementary Schools is better than